Hydraulical Approach in Designing of Proportional Division Structures in Traditional Irrigation Schemes - M. Hasan Yahya (PERTETA, 2009)
To disribute water in equal and adequate ways among the farmers, farmers have been using a proportionaldivision structure for years. The constrtuction of the structure is made of wood or stone with the notchsin rectangular form in part of its upper side. Its performance criterion estabilished by pertinient famers i.e.the notch width has to be proportional to the size of its command area. From hydraulic point of view,however, the unreliability of these structures can be occurred and it was estimated that their performancecriteria not only depend on the notch width but also the other hydraulic design criteria. The objectives ofthis research are: (i) to comprehend the dependence of performance of a proportional division structureon hydraulic design criteria, (ii) to know relationships between the discharge of structure and the hydraulicdesign criteria. Result of experiment indicated that the performance of a proportional division structure notonly depend on notch width but also the other hydraulic design criteria in common. In general, there werethe relationships between discharge of a notch and the hydraulic design criteria including notch width,thickness and surface roughness of the structure, and deviation angle of channel where the structure to belocated.Keywords: traditional Irrigation system, proportional devision structure, physical model, dimension analysisDiterima: 3 Maret 2009; Disetujui: 7 Agustus 2009